Syagrus amicorum, a new Arecaceae from Bahia, Brazil - Soares, Kelen Pureza; Guimarães, Carlos Alex Lima (Phytotaxa, 2019)
Syagrus amicorum, a new Arecaceae species is described and illustrated. This species occurs in the state of Bahia, Brazil. Data on habitat, ecology, etymology, geographical distribution, morphological affinity and status of conservation according to the IUCN criteria are provided.